Characterization and Modeling Study on Softening and Seepage Behavior of Weakly Cemented Sandy Mudstone after Water Injection. (7th December 2021) - Guo, Junting; Teng, Teng; Zhu, Xiaoyan; Wang, Yuming; Li, Zhaolong; Tan, Yi
Abstract : Water injection-induced rock softening and the associated water seepage characteristics are the common and basic problems in underground reservoir construction and the prevention of mine water disaster. In this paper, a series of experimental studies was carried out to investigate these characteristics with the weakly cemented sandy mudstone collected from Shendong Buertai coal mine, China. The characteristics of water softening and the stress-seepage interactions in water-saturated weakly cemented sandy mudstone were directly obtained. Then, a modification method of the constitutive model for rock mass considering the softening effect and a stress-damage-driven model for permeability evolution were established. Research results show that water saturation reduces the tensile strength, compressive strength, and cohesion by 56% and reduces the elastic modulus by 28%. The hydraulic effects on Poisson's ratio and internal friction angle are negligible. The relationship between the permeability of weakly cemented sandy mudstone with complete compaction deformation is to be divided into three stages of seepage shielding, seepage surge, and seepage recovery. Rock permeability in each stage has a negative exponential relationship with the effective stress. This research provides a theoretical basis for the researches of hydromechanical couplings on weakly cemented sandy mudstone, which is insightful for rock engineering practice.